Early hydrogen excretion peaks during breath tests. Small intestinal bacterial overgrowth or accelerated transit?. Issue 4 (April 2021) - Vernia, Piero; Cesarini, Monica; de Carolis, Aurora; Vernia, Filippo
Abstract: Background: Small intestinal bacterial overgrowth (SIBO) has been reported with varying prevalence, depending upon the criteria used for diagnosis. Lactulose and glucose breath tests are the most used in clinical settings. Early rises of hydrogen excretion during a lactose breath test suggest SIBO, but the finding could result from accelerated mouth-to-caecum transit time. Aims: Defining the prevalence of early hydrogen peaks during lactose breath tests and assessing the proportion of patients affected by SIBO. Methods: An early (≤ 60′) hydrogen excretion peak was observed in 120/663 patients with positive lactose hydrogen breath test. Eighty-one of them underwent a 50 g-9sample-glucose hydrogen breath test to diagnose SIBO. Results: The glucose breath test proved positive in 11/81 (13.6%) patients. The positivity rate was 18.2% (2/11) in those with the first peak detected at 30′ and 12.8% (9/70) in those with the peak occurring at 60′. Conclusions: Early hydrogen excretion peaks are rarely associated with SIBO. The low positive predictive value indicates that the finding does not help identifying patients at high risk for this condition. Indirectly, the present data support the opinion that the prevalence of SIBO diagnosed by standard lactulose breath tests is much lower than reported, and the reliability of the test is low.